Investigation of the redox-conditions in the Nam Du well field, Hanoi, Vietnam, and their implications for mobilisation of arsenic - Moreskog, Johanna (2008)
In 2005, a new well field along the Red River started pumping groundwater for production of drinking water in the Nam Du area south of Hanoi, Vietnam. Elevated concentrations of ammonium have been a well-known problem in the southern part of Hanoi area, but recently elevated concentrations of arsenic in the groundwater has also been of concern. The first study on elevated concentrations of arsenic in the Red River delta was published in 2001 (Berg et al., 2001). Peat has been discussed as a source for both ammonium and as a driver for the mobilisation of arsenic and this study aims to investigate the possible relationship between arsenic, ammonium, the peat and the redox conditions. Chemical analyses from this study resulted in total arsenic concentrations from 27 to 312 Î¼g/l in the groundwater samples, which can be compared to the health-based guideline of 10 Î¼g/l. Most of the arsenic in the groundwater is present as arsenite, the more toxic specie of arsenic. The analyses also showed elevated concentrations of ammonium in the groundwater ranging from 1.8 to 34.7 mg/l. The relationships between the different redox couples were studied with Visual Minteq, which showed that the redox potentials measured in the field were a little bit higher than expected from the model. This can probably be explained by contamination of oxygen during sampling and/or measurement. The lack of sulphate in combination with the present redox conditions indicated that oxidation of arsenic bearing sulphurous minerals is not likely to be the main source of arsenic. Instead, the relationship between arsenic and HCO3, indicates that a more probable source of the arsenic would be reductive dissolution of iron oxyhydroxides.